What a difference trade makes: Export activity and the flexibility of collective bargaining agreements - Wolf Dieter Heinbach; Stefanie Schröpfer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
The prevalence of opening clauses in collective bargaining agreements may indicate a tendency towards more decentralised wage setting. Increasing competition on international product markets is assumed to be one reason for the decentralisation of collective bargaining. Current theoretical explanations focus merely on firm-level differences in the exposure to international competition. Unlike non-exporting firms, exporters are assumed to be exposed to international competition and are therefore in need of greater wage flexibility. However, incorporating stylised facts about exporting firms, new theoretical trade models suggest that firms differ from each other in how they adjust to increasing competition depending on their export behaviour as a measure of productivity. While large, highly productive exporters expand into new markets, small, low-productive non-exporters are threatened by import competition. Based on a trade model by Bernard et al. (2003), we are able to explain verbally how a decentralisation of wage bargaining arises due to different labour demand reactions of exporters and non-exporters. In contrast to the result assuming differences in the exposure to international competition, we find non-exporters to require greater wage flexibility. As the introduction of opening clauses increases wage flexibility at firm level, we examine empirically whether exporters or non-exporters have a higher probability of using opening clauses. Based on IAB establishment data covering the western German manufacturing sector, our results suggest that firms exporting to EMU countries - but not exporters in general - have a lower propensity for using opening clauses than non-exporters.
Keywords: 330; Tarifvertrag; Öffnungsklausel; Tarifverhandlungen; Dezentralisation; internationaler Wettbewerb; Wettbewerbsfähigkeit; Lohnflexibilität; IAB-Betriebspanel; verarbeitendes Gewerbe; Außenhandel; Export - Auswirkungen; Westdeutschland; Bundesrepublik Deutschland